Репродукція як один із факторів стійкості популяцій рідкісних видів рослин - Клименко, Ганна; Коваленко, Ігор; Klimenko, Anna; Igor, Kovalenko (Східноєвропейський національний університет імені Лесі Українки, 2016)
Проведено дослідження репродукції семи видів рідкісних рослин (Epipactis helleborine, Listera ovata, Platanthera chlorantha, Circaea alpine, Lilium martagon, Pulsatilla patens і Pyrola chlorantha) в умовах НПП «Деснянсько-Старогутський». Найменший внесок у репродукцію характерний для Lilium martagon, а найбільший – Pulsatilla patens. The study of reproduction of seven rare plant species (Epipactis helleborine, Listera ovata, Platanthera chlorantha, Circaea alpine, Lilium martagon, Pulsatilla patens and Pyrolachlorantha) is conducted in the conditions of the National Nature Park “Desniansko-Starogutsky”. It covers more than 700 individuals with the use of non-destructive methods of morphometry. Reproductive effort is determined as the ratio of quantitative indicators and leaf-area duration. It has been found out that Pulsatilla patens is the most successful species in reproduction. Reproductive effort of this species reaches almost 500 %, because Pulsatilla patens reproduces primarily by seed. Lilium martagon is characterized by the least contribution to reproduction (1,05 %). Among three representatives of the Orchidaceae family, Listera ovata has made the greatest contribution to reproduction (RE is equal to 30,15 %), and in Platanthera chlorantha and Epipactis helleborine this indicator do not exceed 15 %. Quite a high level of reproductive effort is observed in C.аlpinе and Pyrola chlorantha, although the latter is dominated by vegetative reproduction.
Reproduction as a Factor of the Sustainability of Rare Plant Species
Keywords: рідкісні види; морфометрія; неруйнуючі методи; репродуктивне зусилля; репродукція; rare species; morphometry; non-destructive methods; reproductive effort; reproduction